2011
DOI: 10.1111/j.1742-4658.2011.08122.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the nucleocytoplasmic lectin ‘Orysata’ from rice in Pichia pastoris

Abstract: The Oryza sativa lectin, abbreviated Orysata, is a mannose‐specific, jacalin‐related lectin expressed in rice plants after exposure to certain stress conditions. Expression of a fusion construct containing the rice lectin sequence linked to enhanced green fluorescent protein in Bright Yellow 2 tobacco cells revealed that Orysata is located in the nucleus and the cytoplasm of the plant cell, indicating that it belongs to the class of nucleocytoplasmic jacalin‐related lectins. Since the expression level of Orysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Over the last 5 years at least eight (Jiang et al, 2010) types of lectin domain have been reported in rice, most of which can be considered as stress-inducible lectins. The jacalin-related lectin Orysata and the EUL-related lectin OrysaEULS2 have both been shown to exhibit specificity towards mannose (Al Atalah et al, 2011. This report yields evidence that at least OrysaEULD1A is directed towards galactosylated carbohydrates.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Over the last 5 years at least eight (Jiang et al, 2010) types of lectin domain have been reported in rice, most of which can be considered as stress-inducible lectins. The jacalin-related lectin Orysata and the EUL-related lectin OrysaEULS2 have both been shown to exhibit specificity towards mannose (Al Atalah et al, 2011. This report yields evidence that at least OrysaEULD1A is directed towards galactosylated carbohydrates.…”
Section: Discussionmentioning
confidence: 60%
“…The full EULD1A sequence from rice as well as its individual EUL domains EULD1A domain 1 and EULD1A domain 2, have been successfully expressed in P. pastoris. On average, the yield obtained for the recombinant proteins can be considered low compared to the yield reported previously for some other plant lectins (Oliveira et al, 2008;Al Atalah et al, 2011). However a yield of 0.5-3 mg/l recombinant protein is comparable to the yield obtained for OrysaEULS2 (4-6 mg/l) (Al Atalah et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations